ORIGAMI AS AN EDUCATIONAL TOOL AND ITS EFFECT ON THE DEVELOPMENT OF SCHOOL STUDENTS - Mohd Salehudin Marji; Nor Aisyah Che Derasid; Aede Hatib Musta'amal; Ade Aliff Jobin (Jurnal Scientia, 2023)
In recent years, origami has also made its way into the field of education. Many countries have implemented origami in their educational curricula due to its numerous benefits for student development. Origami has been found to help students in many ways, including the development of cognitive, social, and motor skills. To investigate the effects of origami on student development, a study was conducted using a systematic literature review method. The study focused on articles published between 2018 and March 13, 2023, and utilized keywords such as "origami," "education," "student development," "cognitive skills," "social skills," and "motor skills." Six article selection criteria were established before the selection process, ensuring that only the most relevant and reliable sources were included. For instance, origami was found to be effective in improving students' math and geometry skills. Through the folding of paper, students were able to develop their spatial reasoning, geometric thinking, and problem-solving abilities. Additionally, origami was found to enhance students' fine motor skills, which are essential for various activities, such as writing and drawing. Origami also had a positive impact on students' psychology and emotion, as it provided a calming and relaxing activity that can help students reduce stress and anxiety. Furthermore, origami was found to foster creativity and critical thinking, as it requires students to think creatively and strategically when designing their paper creations.